Evidence for two progesterone receptor binding sites in murine mammary carcinomas - Helguero, Luisa A. (2003)
We have evaluated the progesterone receptor (PR) binding patterns in progestin-dependent and -independent murine mammary carcinomas; all variants regress completely after antiprogestin treatment. These studies revealed the presence of a high affinity, low capacity-binding site (K(d): 43 +/- 9 pM; Q=9 +/- 3 fmol/mg protein) and of the classical lower affinity, high capacity-binding site (K(d): 9.2 +/- 4.2 nM; Q=376 +/- 64 fmol/mg protein). These sites could also be detected in uterus. Antiprogestins were able to bind to both sites. In vitro, medroxyprogesterone acetate (MPA) was stimulatory along a biphasic curve with two slopes, one at very low concentrations (EC(50): 1.5 +/- 0.7 fM) and the other at values compatible with the described K(d) for the PR (EC(50): 0.33 +/- 0.3 nM).